DOI: 10.14264/731b55c
|View full text |Cite
|
Sign up to set email alerts
|

UQ eSpace

Abstract: Tissue engineered (TE) bone scaffold is a three-dimensional porous structure that is implanted to allow for accelerated regeneration of bone tissue in the patient. This is achieved by providing the high internal surface area required for cell adhesion and consequent growth. Additive manufacturing techniques such as selective laser sintering (SLS) offer high tunability of scaffold properties. Previous studies have focussed on pre-designed scaffold architectures to achieve the desired pore characteristics throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Rises in temperature will generally be greatest in the South East and least in the North West [42]. While higher overall temperatures should favour the planting of eucalypts, other factors, such as enhanced atmospheric carbon dioxide levels may increase the risk of frost damage in evergreens like eucalypts [43] and this has been shown in experiments with E. pauciflora [44]. This observation is supported by other studies, which have shown that increased atmospheric CO 2 delays acclimation in autumn (Coreys et al 2006 in [42]) and accelerates the loss of cold-hardiness in spring [42].…”
Section: Eucalypts As a Productive Wood Fuel Resourcementioning
confidence: 99%
“…Rises in temperature will generally be greatest in the South East and least in the North West [42]. While higher overall temperatures should favour the planting of eucalypts, other factors, such as enhanced atmospheric carbon dioxide levels may increase the risk of frost damage in evergreens like eucalypts [43] and this has been shown in experiments with E. pauciflora [44]. This observation is supported by other studies, which have shown that increased atmospheric CO 2 delays acclimation in autumn (Coreys et al 2006 in [42]) and accelerates the loss of cold-hardiness in spring [42].…”
Section: Eucalypts As a Productive Wood Fuel Resourcementioning
confidence: 99%